Phases of Development of Regional Airports in Poland and other Central-Eastern European Countries, after Accession to the European Union - Pijet-Migoń, Edyta (Studia Oeconomica Posnaniensia, 2016)
The Polish accession to the European Union, and the related liberalization of air transport, has caused a range of changes on the air passenger market, including the development of regional airports. This paper aims to show the evolution of Polish regional airports and to compare them with changes experienced by regional airports in other Central-Eastern European countries. The latter include countries which joined the EU both along with Poland (Czech Republic, Estonia, Hungary, Latvia, Lithuania, Slovakia) and at a later date (Bulgaria, Romania). The key research question is whether development trends experienced at regional airports in various countries were similar or different. The Eurostat database, data from civil aviation authorities, and information from airports themselves were used in the comparative analysis. Connection networks were examined using past and contemporary flight timetables. Differences between countries and airports have a mainly quantitative character, reflecting the size of a country (area, population), but a clear three-stage temporal pattern of expansion, followed by crisis and then consolidation, emerges in most countries. These phases of development do not typify Central-Eastern Europe only, but were also characteristic for markets that were de-regulated earlier (USA, western Europe). However, the duration of each phase in Central-Eastern Europe was markedly shorter.